Developing Product Environmental Footprint Category Rules (PEFCR) for shampoos: The basis for comparable life cycle assessment. (5th August 2018) - Golsteijn, Laura; Lessard, Lindsay; Campion, Jean‐Florent; Capelli, Alexandre; D'Enfert, Virginie; King, Henry; Kremer, Joachim; Krugman, Michael; Orliac, Hélène; Furnemont, Severine Roullet; Schuh, Werner; Stalmans, Mark; et al.
ABSTRACT: In 2013, the European Commission launched the Environmental Footprint Rules pilot phase. This initiative aims at setting specific rules for life cycle assessment (LCA: raw material sourcing, production, logistics, use, and disposal phase) studies within 1 product category, called product environmental footprint category rules (PEFCR), and for organizations, called organizational environmental footprint sector rules (OEFSR). Such specific rules for measuring environmental performance throughout the life cycle should facilitate the comparability between LCA studies and provide principles for communicating environmental performance, such as transparency, reliability, completeness, and clarity. Cosmetics Europe, the association representing the cosmetics industry in the European Union, completed a voluntary study into the development of PEFCR for shampoo, generally following the guidelines and methodology developed by the European Commission for its own pilot projects. The study assessed the feasibility and relevance of establishing PEFCR for shampoo. Specifically, the study defines a large number of modeling assumptions and default values relevant for shampoo (e.g., for the functional unit, the system boundaries, default transport distances, rinsing water volumes, temperature differences, life cycle inventory data sources) that can be modified as appropriate, according to the specificities of individual products, manufacturing companies, and countries. The results of the study may be used to support internal decision making (e.g., to identify "hotspots" with high environmental impact and opportunities for improvement) or to meet information requests from commercial partners, consumers, media, or authorities on product environmental characteristics. In addition, the shampoo study also highlighted many of the challenges and limitations of the current product environmental footprint (PEF) methodology, namely its complexity and resource intensiveness. It highlighted 2 areas where improvements are much needed: (1) data quality and availability, and (2) impact assessment methodologies and robustness. Many of the findings are applicable to other rinse‐off cosmetic products, such as shower gels, liquid soaps, bath products, and hair conditioners. Integr Environ Assess Manag 2018;14:649–659. © 2018 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: We show that the energy consumed to heat water is one of the largest contributions to the overall effect of shampoo. The current study also resulted in default values for all life cycles stages. The PEFCR documentation provides justifications for all choices made, including references to important information sources that can be consulted for more information. In the case of limited data availability for LCAs on other cosmetics, the values presented in the current study can be used as proxies or the literature referred to can be consulted for guidance otherwise. Next to the results and default values, the current study also resulted in important findings regarding the effect of the data quality, the general level of precision of PEF calculations, and the limitations regarding application of PEF results.